VEDAS AND BUDDHISM: THE HEART OF ANCIENT ETHICAL SYSTEMS - Sivasai, Chintala Venkata (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Vedic ethics are grounded in ideas such as Satya and Rta. In the Vedas and later sutras, the term Satya (सत्य) loses its original meaning and becomes an ethical concept of truthfulness, which is considered a vital virtue. To be accurate to and consistent with reality means to act, speak, and think in such a way. The three pillars of ancient Indian ethics—metaphysical, sociological, and psychological—are found in the Vedas. The metaphysical foundation of Vedic ethics is Rta. Ashrama Dharma is the psychological foundation of Vedic ethics, while Varna Dharma is its sociological foundation.Buddha defined ethics as a set of rules that imitates an innate, natural state characterized by harmony, composure, and self-control and is essentially driven by nonviolence or the desire to avoid harming. It has been defined as morality, skilful conduct, uprightness and precept, and virtue